ANALISIS PENDAPATAN PETANI KELAPA SAWIT SEBELUM DAN SELAMA COVID-19 (STUDI KASUS: KABUPATEN PADANG LAWAS UTARA) - Githa Noviana; Fani Ardiani (MEDIAGRO, 2020)
The COVID-19 outbreak has a negative impact on various business sectors, including plantations. This research was conducted to find out if COVID-19 affects smallholders ' income. Research was conducted in North Padang Lawas, North Sumatera. The samples used in the study were a number of 15 oil palm farmers taken randomly. The primary data collected is the harvest data and sales of farmers before the pandemic COVID-19 from January to June 2019 and pandemic COVID-19 data which is January to June 2020. Total data obtained is 72 production data during the period before COVID-19 and when COVID-19. The Data is analyzed using a comparison analysis to see if there is a difference in farmer's income before and during COVID-19 in the first half of 2019 and 2020. The results of this study showed there was a very significant difference in farmer's income before and during pandemic COVID-19. The farmer's income also declined from January to June 2020. As such, there needs to be a farmer's effort to find additional income during the COVID-19. Keywords: Oil palm; Farmers; Livelihoods; COVID-19; North Sumatera